2022
DOI: 10.1101/2022.08.26.505481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overlapping local and systemic defense induced by an oomycete fatty acid MAMP and brown seaweed extract in tomato

Abstract: Eicosapolyenoic fatty acids are integral components of oomycete pathogens that can act as microbe-associated molecular patterns (MAMPs) to induce disease resistance in plants. Defense inducing eicosapolyenoic fatty acids include arachidonic (AA) and eicosapentaenoic acids, and are strong elicitors in solanaceous plants with bioactivity in other plant families. Similarly, extracts of the brown seaweed, Ascophyllum nodosum, used in sustainable agriculture as a biostimulant of plant growth, may also induce diseas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…Through RNA sequencing, this same study revealed a striking level of transcriptional overlap in the gene expression profiles of AA-or ANE-root-treated tomato across tested timepoints (Lewis et al 2022). Gene ontology functional analysis of transcriptomic data revealed AA and ANE enriched similar categories of genes with nearly perfect overlap also observed in categories of Domonique C. Lewis Phytopathology under-represented genes.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Through RNA sequencing, this same study revealed a striking level of transcriptional overlap in the gene expression profiles of AA-or ANE-root-treated tomato across tested timepoints (Lewis et al 2022). Gene ontology functional analysis of transcriptomic data revealed AA and ANE enriched similar categories of genes with nearly perfect overlap also observed in categories of Domonique C. Lewis Phytopathology under-represented genes.…”
Section: Introductionmentioning
confidence: 75%
“…Previous transcriptomic work revealed a high level of congruency in differentially expressed genes in AA- and ANE-treated tomato seedlings compared to H 2 O-treated controls (Lewis et al 2022). To further this line of investigation, the metabolomic profiles of AA- and ANE-root-treated plants were compared to H 2 O after 24-, 48-, 72-, and 96-hours exposure to their respective treatments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations